2014
DOI: 10.1002/rcm.7031
|View full text |Cite
|
Sign up to set email alerts
|

The formation of [M–H]+ ions in N‐alkyl‐substituted thieno[3,4‐c]‐pyrrole‐4,6‐dione derivatives during atmospheric pressure photoionization mass spectrometry

Abstract: [M-H](+) ions were detected in all the TPD derivatives studied here under the special experimental conditions during APPI, using a halogenated benzene dopant, and TPD containing substituted N-alkyl side chains with a minimum of four carbon atoms. Density functional theory calculations showed that for [M-H](+) ions to be formed under these conditions, the loss of hydrogen molecules from the [M + H](+)  ions is proposed to be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Surprisingly [M-H] + and M +∙ peaks were observed in almost all investigated compounds instead of [M+H] + peaks which are observed only in 5c (Figure S48) and 5d (Figure S49) spectra, this indicated that these type of compounds produce [M-H] + , [M-H-H 2 ] + , [M-H 2 ] + and M +∙ positive ions by this soft ionization technique ( Table 2 ). [M-H] + peak is observed in all spectra which may appear due to; a) transfer of hydrogen atom from radical cation of analyte or b) by hydride removal from neutral molecule of analyte, or c) removal of H 2 from protonated molecule of analyte [ 69 , 70 , 71 , 72 ] All these three mechanisms may occur simultaneously or not depending on the structure of analyte molecule [ 73 ]. M +∙ observed in spectra of 5b, 5d, 5h, 5k and 5m (Figures S47, S49, S53, S56 and S58) may be due to photoionization process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly [M-H] + and M +∙ peaks were observed in almost all investigated compounds instead of [M+H] + peaks which are observed only in 5c (Figure S48) and 5d (Figure S49) spectra, this indicated that these type of compounds produce [M-H] + , [M-H-H 2 ] + , [M-H 2 ] + and M +∙ positive ions by this soft ionization technique ( Table 2 ). [M-H] + peak is observed in all spectra which may appear due to; a) transfer of hydrogen atom from radical cation of analyte or b) by hydride removal from neutral molecule of analyte, or c) removal of H 2 from protonated molecule of analyte [ 69 , 70 , 71 , 72 ] All these three mechanisms may occur simultaneously or not depending on the structure of analyte molecule [ 73 ]. M +∙ observed in spectra of 5b, 5d, 5h, 5k and 5m (Figures S47, S49, S53, S56 and S58) may be due to photoionization process.…”
Section: Resultsmentioning
confidence: 99%
“…ions by this soft ionization technique (Table2). [M-H] þ peak is observed in all spectra which may appear due to; a) transfer of hydrogen atom from radical cation of analyte or b) by hydride removal from neutral molecule of analyte, or c) removal of H 2 from protonated molecule of analyte[69,70,71,72] All these three mechanisms may occur simultaneously or not depending on the structure of analyte molecule[73]. M þ• observed in spectra of 5b, 5d, 5h, 5k and 5m (Figures S47, S49, S53, S56 and S58) may be due to photoionization process.…”
mentioning
confidence: 99%
“…No particular trend was observed except that the analyte with highest proton affinity dominated the spectrum for mixture samples. For hydrocarbon analytes, both M +• and [M – H] + species were often observed together. , …”
Section: Resultsmentioning
confidence: 99%
“…For hydrocarbon analytes, both M +• and [M − H] + species were often observed together. 52,53 Quantification and Direct Biofluid Analysis. As already shown, vapor pressure is not a limiting factor in contained nAPCI MS.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…It was even possible to detect the deprotonated molecule ([M‐H] + ) at m / z 473.2, which is rather common for tertiary amines. The formation of [M‐H] + is considered to occur through three possible mechanisms: (1) hydrogen atom transfer from the analyte radical cation, (2) loss of H 2 from the protonated analyte, or (3) hydride abstraction from the neutral analyte molecule . These mechanisms could be occurring simultaneously or not, depending on the analyte molecular structure.…”
Section: Resultsmentioning
confidence: 99%